High resistance of fish pathogenic viruses to UV irradiation and ozonated seawater - Liltved, H.; Vogelsang, C.; Modahl, I.; Dannevig, B.H. (Aquacultural engineering, 2006)
Important fish pathogenic viruses, including infectious pancreatic necrosis virus (IPNV), Atlantic halibut nodavirus (AHNV) and infectious salmon anaemia virus (ISAV), were exposed to ultraviolet (UV) irradiation or ozonated seawater in a laboratory model system. Inactivation curves were obtained, and the occurrence of oxidants and ozonation by-products (OBP), including their removal by granular activated carbon (GAC) filtration, was studied. In ISAV, 99.9% inactivation was obtained by an UV dose of 7.7mJ/cm2. The corresponding figures for AHNV and IPNV were 105 and 246mJ/cm2, respectively. In ozonated seawater, total residual oxidants (TRO) were assayed by the DPD colorimetric method. The CT value (the product of TRO concentration and contact time) was calculated from the average TRO concentration (as mg Cl2/l) during the respective contact time (s). 90% reductions in virus titers were obtained by CT values of 1.4(mgs)/l for ISAV, 1000(mgs)/l for AHNV and 1944(mgs)/l for IPNV. The results of this study demonstrate a wide span in UV and TRO resistance among the viruses tested. ISAV was sensitive to both methods, while high resistance in AHNV and IPNV was experienced. The TRO resistance in IPNV and AHNV contradict earlier published results and suggests reconsideration of existing ozonation practise to inactivate these viruses in seawater. Considerably higher CT values than previously reported seem to be required. These discrepancies in results between studies clearly demonstrate the need for development of a standard procedure to conduct inactivation experiments and to develop improved analytical techniques to determine individual oxidants in seawater. Of the detected carcinogenic OBPs, bromate was found in concentrations of 50 and 70μg/l after a contact time of 20 and 80min, respectively, at a TRO concentration of 0.9mg/l. Bromoform was the only trihalomethane (THM) found in significant amount. The bromoform concentration of 16.4μg/l measured after 80min contact time was reduced to 1.6μg/l by GAC filtration with an empty bed contact time (EBCT) of 4.2min. TRO and bromate was reduced below the detection limit after GAC filtration. However, long-term filtration experiments were not conducted. Such experiments should be conducted to determine the adsorptive capacity of GAC for bromate- and THM-removal in ozonated seawater.